Participation in subsistence activities and maintenance of traditional skills among indigenous youth in the South Rupununi, Guyana - van Vliet, Nathalie; Millar, Neal; Melville, Alyssa; David, Oswin; Ignacio, Leroy (Ethnobiology and Conservation, 2022)
Over the past few decades, issues including globalization and the transition to the cash economy have increasingly hindered the transmission of Traditional Ecological Knowledge (TEK) in Indigenous communities throughout the world. The imparting of TEK across generations of Indigenous Peoples is essential in sustaining cultural practices and to maintaining their subsistence lifestyles. In this study, we used semi-structure interviews to assess the level of participation in subsistence activities and acquisition of subsistence skills among Indigenous children in Guyana. We also assessed whether the level of participation or acquisition of skills was explained by location and social characteristics such as age, gender, occupation of mother/father. We found that Indigenous children in the South Rupununi are highly involved in subsistence activities and the majority conserves subsistence related skills. Traditional gears, such as the bow and arrow are still dominant among Indigenous children in South Rupununi, particularly for hunting purposes, but also for fishing. Results also suggest that children’s participation (through work or play) in subsistence activities are key to the acquisition of subsistence knowledge and skills. Among indigenous children in South Rupununi, participation to subsistence activities varies according to gender and is linked to the main occupation of the parents. While participation in subsistence activities is primarily motivated by the need to search for food, those activities are also explicitly described as providing opportunities for skill development and as sources of fun or amusement. The study concludes by advocating the need to revive connections to subsistence ways of life and the integration of more situated learning experiences within the regular school curriculum for indigenous youth.